Surface plasmon excitation and manipulation in disordered two-dimensional nanoparticle arrays - Coello, Víctor; Cortes, Rodolfo; García Ortiz, César Eduardo; Elizondo V., Nora (2013)
We present experimental and numerical results of simultaneous surface plasmon polariton (SPP) excitation and in-plane manipulation with random arrays of gold nanoparticles. The recorded images were obtained by using leakage radiation microscopy (LRM) for the excitation wavelength of 633 nm and for di®erent densities of particles. The numerical model makes use of a composed analytic Green dyadic which takes into account near- and far-¯eld regions, with the latter being approximated by the part describing the scattering via excitation of SPP. The LRM optical images obtained are related to the calculated SPP intensity distributions demonstrating that the developed approach can be successfully used in studies of systems of closely spaced arrays.